Watching without Judging—Genius Awareness Techniques in Homeopathy - de Laporte, Claudia (Homœopathic Links, 2021)
Homeopathy is a holistic healing method for diseases of body and mind.Homeopathy and awareness-based healing methods have a lot in common. The important aspects of a mental healing process on the part of the treating person are empathic receptiveness, watching without judging and reflecting of the observed contents. On the part of the patient it is non-judgemental watching, catharsis and integration.The subtle watching of body, emotions and thoughts, applied in homeopathy, is closely related to meditative awareness techniques which nowadays are also used in psychotherapy.The reflection of the observed is done in homeopathy more by the resonant remedy than by words. With this individual remedy we ‘recognise’ our patients and we catalyse a cathartic awareness process. The primary objective of this awareness process is to help the patient understand and to accept himself, as he is, and subsequently to relax.While it is known that many mental disorders improve by becoming aware, this is less known for somatic diseases, although there are many studies which show a mental connection for a great part of physical diseases, and therefore similar techniques should work.The most important link between body and soul is the moderation of stressful and sympathetic states.Only in a relaxed parasympathetic state self-healing and repairing mechanisms and the immune system can work effectively and locomotor tensions get relief.Homoeopaths often deny the awareness-based effects of their healing method, because they fear homeopathy to be reduced to placebo medicine, in a time where homeopathy is attacked from many sides. As everywhere in medicine, the placebo effect is invited to ADD itself to the direct impact of our well-chosen remedies. Let us invite also the awareness effects described above, which are far more than only suggestive, by applying them more specifically.Homoeopaths should be proud of their genius and really holistic art of healing, which bundles substantial, psychic and energetic effects in an economical way and with very low side effects.
Keywords: awareness medicine; awareness process; awareness techniques; meditation; psychosomatic medicine; psychotherapy; watching